2018
DOI: 10.20471/acc.2018.57.03.04
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of Low Estrogen and Progesterone Positivity in Luminal B (HER2 Negative) Breast Cancer

Abstract: SUMMARY – Luminal B (HER2 negative) subtype is the most diversiform type of breast cancers, with a high Ki-67 proliferation index (>20%) or/and low progesterone (PR; <20%) with various intensity and distribution of hormone receptors. Considerable difference has also been noticed in disease outcome, wherefore there is the need for a more detailed classification of this tumor subtype. The clinical and pathologic parameters of 147 luminal B (HER2 negative) breast cancers were examined. The expression of hormone r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…Similar to our findings, a recently published study showed that 16% of IHC ER+HER2− BCs could be reclassified as Basal molecular subtypes by multigene expression profiling 24 . Furthermore, studies showed that the ER+HER2− Basal subtype is obviously different from the ER+HER2− Luminal subtype and sometimes similar to the ER‐negative Basal subtype with regard to potential therapeutic sensitivity to systemic therapies 24–26 …”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Similar to our findings, a recently published study showed that 16% of IHC ER+HER2− BCs could be reclassified as Basal molecular subtypes by multigene expression profiling 24 . Furthermore, studies showed that the ER+HER2− Basal subtype is obviously different from the ER+HER2− Luminal subtype and sometimes similar to the ER‐negative Basal subtype with regard to potential therapeutic sensitivity to systemic therapies 24–26 …”
Section: Discussionsupporting
confidence: 87%
“… 24 Furthermore, studies showed that the ER+HER2− Basal subtype is obviously different from the ER+HER2− Luminal subtype and sometimes similar to the ER‐negative Basal subtype with regard to potential therapeutic sensitivity to systemic therapies. 24 , 25 , 26 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to St. Gallen Breast Cancer Conference, they are divided into 5 subgroups: Luminal A, Luminal B HER2 negative (LUM B1), Luminal B HER2 positive (LUM B2), HER2 positive (HER2 pos) and triple negative subtype. This division is based on estrogen (ER) and progesterone (PR) receptor and human epithelial growth factor expression ( 5 , 6 ). This classification includes all breast cancer types regardless of their histopathologic group.…”
Section: Introductionmentioning
confidence: 99%
“…Not surprisingly, PR expression serves as a predictive parameter for endocrine therapy response [ 47 ]. In many cases, as HR+ tumors progress, many lose ER and/or PR expression and, as such, loss of PR expression is associated with a significantly worse prognosis [ 47 , 49 ]. Several studies have indicated that PR loss contributes to an aggressive phenotype as a result of activating a transcriptomic profile which includes increased EGFR and NOTCH1 signaling as well as expression of genes that regulate amino acid uptake.…”
Section: Introductionmentioning
confidence: 99%